The Oxidative Metabolism of Fossil Hydrocarbons and Sulfide Minerals by the Lithobiontic Microbial Community Inhabiting Deep Subterrestrial Kupferschiefer Black Shale - Włodarczyk, Agnieszka; Lirski, Maciej; Fogtman, Anna; Koblowska, Marta; Bidziński, Grzegorz; Matlakowska, Renata (Frontiers in Microbiology, 2018)
Black shales are one of the largest reservoirs of fossil organic carbon and inorganic reduced sulfur on Earth. It is assumed that microorganisms play an important role in the transformations of these sedimentary rocks and contribute to the return of organic carbon and inorganic sulfur to the global geochemical cycles. An outcrop of deep subterrestrial ~256-million-year-old Kupferschiefer black shale was studied to define the metabolic processes of the deep biosphere important in transformations of organic carbon and inorganic reduced sulfur compounds. This outcrop was created during mining activity 12 years ago and since then it has been exposed to the activity of oxygen and microorganisms. The microbial processes were described based on metagenome and metaproteome studies as well as on the geochemistry of the rock. The microorganisms inhabiting the subterrestrial black shale were dominated by bacterial genera such as Pseudomonas, Limnobacter, Yonghaparkia, Thiobacillus, Bradyrhizobium and Sulfuricaulis. This study on black shale was the first to detect archaea and fungi, represented by Nitrososphaera and Aspergillus genera, respectively. The enzymatic oxidation of fossil aliphatic and aromatic hydrocarbons was mediated mostly by chemo-organotrophic bacteria, but also by archaea and fungi. The dissimilative enzymatic oxidation of primary reduced sulfur compounds was performed by chemolithotrophic bacteria. The geochemical consequences of microbial activity were the oxidation and dehydrogenation of kerogen, as well as oxidation of sulfide minerals.